Penerapan Budidaya Melati Berdasarkan Gap di Kawasan Florikultura Jingah Habang Ilir Kabupaten Banjar - Hilda Susanti; Indriani Indriani (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
The community service activity entitled the application of jasmine cultivation based on the gap in the Jingah Habang ilir floriculture area of Banjar district was carried out on September 12, 2019. This activity was carried out in the form of training with lecture methods, discussions/questions and answers, and quizzes. This activity aims to (1) provide knowledge and guidance to farmers regarding jasmine cultivation based on GAP, (2) assist local governments in developing floriculture areas in Banjar Regency. The target audience of this community service activity are jasmine producing farmers in the floriculture area of Jingah Habang Ilir village, Karang Intan district, Banjar district, South Kalimantan. The results of community service were measured descriptively from the responses given during the training activities, as well as from the follow-up carried out by producer farmers after the training. Follow-up by producer farmers is seen from filling out questionnaires carried out by 10 producer farmers in 2021. The level of achievement can be achieved through changes in thinking and attitudes in carrying out jasmine cultivation based on GAP. Based on the findings in this community service activity, it can be seen that the jasmine cultivation that has been carried out by producer farmers only uses empirical science, namely science based on the experience of ancestors, as well as "trial and error" that occurs in the field. The evaluation carried out after 1.5 years of training in 2021 showed that the implementation of the GAP for jasmine cultivation that had been carried out by farmers was 100% having carried out land management both using machines and human power. Farmers have prepared the seeds according to the recommendation, namely 90% have used stem cuttings with a brownish green color. Farmers have provided complete fertilizer containing N, P, and K, of which 40% have fertilized 3 times a year.  Farmers still need assistance to apply GAP to other components of cultivation practices to make the floriculture area in Banjar district sustainable.